Smart EV Charger With Reactive Power Compensation and Surge Protection - Bhandari, Nirajan; Pandey, Pratik; Adhikari, Bibek; Dhungel, Ashish; Thapa, Deepak; Ghimire, Ankit (Amrit Research Journal, 2024)
The paper proposes integrating compensating functions into fast EV charging stations to enhance grid reliability and reduce reliance on costly devices like STATCOMs and Capacitor Banks used to solve voltage drop issues caused by EV adoption. The developed smart fast EV charger functions as a boost rectifier while simultaneously providing surge protection and compensating reactive power in the grid during charging. Using a cross-coupling strategy, a PID controller manages the leading current to supply reactive power to regulate voltage at the connection node. An ILPS with SPD safeguards the charger from lightning or other induced surges. The charger can operate in three modes: charging the battery at unity power factor, acting as a STATCOM without connecting the battery, or charging the battery while supplying reactive power to the grid in a bidirectional manner.